2007
DOI: 10.1021/ct600366k
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Parallel Coupled Cluster Calculations:  Combining Distributed and Shared Memory Techniques for Modern Cluster Based Systems

Abstract: A parallel coupled cluster algorithm that combines distributed and shared memory techniques for the CCSD(T) method (singles + doubles with perturbative triples) is described. The implementation of the massively parallel CCSD(T) algorithm uses a hybrid molecular and "direct" atomic integral driven approach. Shared memory is used to minimize redundant replicated storage per compute process. The algorithm is targeted at modern cluster based architectures that are comprised of multiprocessor nodes connected by a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 61 publications
9
131
0
Order By: Relevance
“…They found that CCSD(T) predicted the relative energy spacings to be slightly larger than MP2 but that both methods predicted the same energy ordering. We note that MP2 is commonly used 6,[43][44][45] for benchmark energies of water oligimers when CCSD(T) is too expensive, but in the present case, we used new state-of-the-art capabilities 42 to calculate benchmark results at the higher CCSD(T) level.…”
Section: Introductionmentioning
confidence: 99%
“…They found that CCSD(T) predicted the relative energy spacings to be slightly larger than MP2 but that both methods predicted the same energy ordering. We note that MP2 is commonly used 6,[43][44][45] for benchmark energies of water oligimers when CCSD(T) is too expensive, but in the present case, we used new state-of-the-art capabilities 42 to calculate benchmark results at the higher CCSD(T) level.…”
Section: Introductionmentioning
confidence: 99%
“…2͔͒ are very distinct and close to each other and to earlier CCSD͑T͒ results. 16 These trends cannot be accounted for by DFT with traditional GGA ͓PBE ͑Ref. 17͒, RPBE ͑Ref.…”
mentioning
confidence: 99%
“…Energies for all species are presented using closed or spin-restricted open shell MP2 [10,11]. For singlets, a parallel CCSD(T) program [107] could be used to check the MP2 results. CCSD(T) energies, where available, are given in parentheses after the MP2 energies.…”
Section: A Methodsmentioning
confidence: 99%